Multiple sclerosis - Hafler, David A. (American Society for Clinical Investigation, 2004)
Multiple sclerosis is a complex genetic disease associated with inflammation in the CNS white matter thought to be mediated by autoreactive T cells. Clonal expansion of B cells, their antibody products, and T cells, hallmarks of inflammation in the CNS, are found in MS. This review discusses new methods to define the molecular pathology of human disease with high-throughput examination of germline DNA haplotypes, RNA expression, and protein structures that will allow the generation of a new series of hypotheses that can be tested to develop better understanding of and therapies for this disease.